Writing games : multicultural case studies of academic literacy practices in higher education - Casanave, Christine Pearson, 1944- (Lawrence Erlbaum Associates, 2002)
This work explores how writers from several different cultures learn to write in their academic settings, and how their writing practices intersect with their evolving identities as students and professionals in academic environments.